The convergence of the performing and creative arts : reimagining methodologies and traditions - Tan, Sooi Beng (Proceedings series / Penerbit USM, 2013)
"This edited volume forms a compilation of new works on architecture, fine arts, crafts, film, music, dance, theatre, new media, design, advertising, publishing, research and development software, television and radio, which look at the dynamics and impact of the convergence of the arts within the context of the creative industries. They debate issues of engaging audiences through convergence, participation, collaboration and agency in the transformation of traditions, creation of alternative methodologies, education, digital media and design, as well as representation in the creative arts. This book promotes dialogue between and across disciplines with a focus on the varied historical, cultural and technological settings in different parts of the world in which convergence is located. The proceedings describe some of the ways that convergence is restructuring culture and society and the relationship between audiences, producers and content in Asia. Convergence involves changes in the methods culture is created and consumed."--Preface and acknowledgements.